ARKEOLOGI EPISTEMIK NARASI PERTENTANGAN AGAMA DAN PANCASILA - Anas, Mohamad; Setyaningsih, Emy; Hasibuan, Albar Adetary (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2023)
This article elaborates on the narrative that contrasts religion and Pancasila which has recently become stronger. This is marked by rejection by some groups who consider Pancasila an idol or taghut that must be fought. On the other hand, some express problematic views, such as in the KPK national test by asking which position is higher, between the Koran and Pancasila. This research is qualitative-descriptive with a hermeneutic approach, namely the researcher describes the narrative of the conflict and interprets it from a reproductive interpretive point of view. The theoretical basis used to obtain a complete picture and analysis of the conflict narrative is Pancasila philosophy, especially Pancasila epistemology. This theory is used to describe the source of the conflicting narrative, the structure of the conflicting narrative, and the validity of the conflicting narrative. The results of this research show that epistemic reproduction in narratives that position religion as higher than Pancasila, or conversely that Pancasila is higher than religion occurs in different forms and networks of power. In the first narrative, epistemic reproduction is intertwined with the ideas of Islamism and religious populism. Meanwhile, in the second narrative, epistemic reproduction is intertwined with the idea of radical nationality because the Republic of Indonesia is dead. The reproduction of the conflict narrative continues to be reproduced, even though in different contexts or times but is the same in terms of the substance of the conflict.